Relation between core strength, core stability, and athletic performance—a mediation analysis approach - Schulte, Sarah; Lukas, Matthias; Bopp, Jessica; Zschorlich, Volker; Büsch, Dirk (Frontiers in Sports and Active Living, 2025)
BackgroundCore strength and its control in movement, also called core stability, are crucial for athletic performance. However, there is no consensus in the scientific literature regarding the extent of the relation between core strength, core stability, and athletic performance. According to the functional anatomy of the core, it seems that core stability indirectly influences the relation between core strength and athletic performance.ObjectivesThis study aimed to examine the relation between core strength, core stability, and athletic performance.MethodsForty-one adult sport students were included in a laboratory study. The subjects participated in two testing sessions. Each testing session started with the Unilateral Landing Error Scoring System (ULESS) test. Single-leg drop jumps were performed on force plates to assess jump height as parameter for athletic performance. Drop jumps were recorded from frontal perspective to analyze kinematic data, i.e., lateral pelvic tilt, lateral trunk lean, and frontal knee angles, to evaluate core stability. A testing session involved either isometric core muscle endurance or maximal core strength and core power measurement in four exercises: flexion, extension, lateral flexion right, and lateral flexion left.ResultsA mediation analysis with multiple predictors and multiple mediators was conducted using standardized z-scores of core strength components as predictors, kinematic parameters of core stability as mediators, and jumping performance as the criterion variable. The mediation analysis revealed no statistically significant indirect effects of the mediators on the relation between core strength and jumping performance. Only a small direct effect [β = 0.19, 95% BCa CI (0.10, 0.27), p < .001] on the relation between maximal core strength and jumping performance was observed.ConclusionsThe results indicate that, at least in our experimental setup, core stability does not appear to mediate the relation between core strength and jumping performance, but maximal core strength shows a relation to jumping performance. Insufficient force transfer of the hip musculature through the kinetic chain of the drop jump may cause the missing mediating effect of core stability. Consequently, hip strength measurement should be included as an additional predictor or mediator alongside core strength or core stability in the mediation model.